Endocarditis: A Diagnostic Challenge - Wilhelmina J. A. R. M. Valckx MD; Suzanne P. M. Lutgens MD, PhD; Hortence E. Haerkens-Arends MD; Peter C. Barneveld MD; Jaap J. Beutler MD, PhD; Ellen K. Hoogeveen MD, PhD (SAGE Publishing, 2017)
A 74-year-old hemodialysis patient with a history of an atrial septum defect closure, coronary bypass surgery, and a St. Jude aortic prosthetic valve was diagnosed with pneumonia and volume overload. Blood cultures were positive for Listeria monocytogenes , and amoxicillin was given for 2 weeks. Immediately after discontinuation of amoxicillin, fever relapsed. Transthoracic and transesophageal echocardiography showed no sign of endocarditis. Given the fever relapse and 3 positive minor Duke criteria, an 18 F-FDG PET-CT scan ( 18 F-fluorodeoxyglucose-positron emission tomography-computed tomography) scan was performed. This scan showed activity at the aortic root, proximal ascending aorta, and inferior wall of the heart, making Listeria monocytogenes endocarditis a likely explanation. Amoxicillin was given for 6 weeks with good clinical result. Diagnosing a life-threatening Listeria monocytogenes endocarditis can be challenging and an 18 F-FDG PET-CT scan can be helpful.